Deception and analogy in the Qur’anic surahs indicating its title on the resurrection: التغريض والمماثلة في السور القرآنية الدال عنوانها على البعث (المجلة العربية للعلوم و نشر الأبحاث, 2021)
The research deals with the study of deception and analogy in the Qur’anic surahs indicating its title on the resurrection, given that it is mentioned in the Holy Qur’an, in contrast to the multiplicity of names of the surahs fixed by the commentators, which are: (Smoke- Al- Jathiyah- Al- Waqi'ah- Al- Thaqabun- Al- Haqqah- Resurrection- Al- Naba- Al- Takwir- Breakup- Al- Shism- Trance- earthquake- knock). The research is based on the relational descriptive approach The study of deception requires revealing the extent to which the beginning of the surah is related to the title, at a time when organizing the verses' sequences in the surah from beginning to end reveals the link between the verses with the title and the starting point, and the link between the end of the surah and its beginning in a coherent whole. The study of analogy also requires a statement between the surahs in question of participation in basic units that reveals the harmony of the surahs related to the resurrection context. This means that the prejudice is related to the internal cohesion and harmony of each surah separately, while the similarity relates to the external cohesion and harmony that connects the surahs in question with each other.